Gut Melatonin in Vertebrates: Chronobiology and Physiology - Mukherjee, Sourav; Maitra, Saumen Kumar (Frontiers in Endocrinology, 2015)
Melatonin, following discovery in the bovine pineal gland, has been detected in several extra-pineal sources including gastrointestinal tract or gut. Arylalkylamine N-acetyltransferase (AANAT) is the key regulator of its biosynthesis. Melatonin in pineal is rhythmically produced with a nocturnal peak in synchronization with environmental light-dark cycle. A recent study on carp reported first that melatonin levels and intensity of a ~23kDa AANAT protein in each gut segment also exhibit significant daily variations but, unlike pineal, show a peak at midday in all seasons. Extensive experimental studies ruled out direct role of light-dark conditions in determining temporal pattern of gut melatoninergic system in carp, and opened up possible role of environmental non-photic cue(s) as its synchronizer. Based on mammalian findings, physiological significance of gut derived melatonin also appears unique because its actions at local levels sharing paracrine and/or autocrine functions have been emphasized. The purpose of this mini-review is to summarize existing data on the chronobiology and physiology of gut melatonin and to emphasize their relation with the same hormone derived in the pineal in vertebrates including fish.